Optimal groundwater management in Pakistan’s Indus Water Basin - Nasim Sanval; Helfand, Steven (International Food Policy Research Institute, 2016)
In this report we examine the management of groundwater in Pakistan’s Indus Basin through a model of groundwater extraction with hydrologic, economic, and tenure constraints. We develop a groundwater extraction model for the Indus Basin and simulate the effect of common property management (the status quo in the Indus Basin) and optimal management on groundwater extractions, water table height, groundwater quality, and annual net benefits from irrigated agriculture. The analysis provides a framework to develop and discuss policies that could lead to the optimal management of groundwater.